Hemoglobin A1C in Charcot: Can It Predict a BKA?. Issue 4 (November 2022) - Martinazzi, Brandon J.; Manto, Kristen; Bonaddio, Vincenzo; Kirchner, Gregory; Nam, Hannah; Aynardi, Michael C.
Category: Diabetes; Ankle; Trauma; Other Introduction/Purpose: Charcot Foot is a serious and potentially limb-threatening complication of longstanding diabetes, peripheral neuropathy, and trauma. One of the many challenges that surgeons face when treating the Charcot Foot is predicting long-term outcomes. Therefore, the purpose of this study was to determine if hemoglobin A1C level was associated with an increased risk of BKA in Charcot Foot patients. Methods: Following institutional board approval, all patients from 2015-2021 with a diagnosis of Charcot Foot were queried using hospital electronic medical records. Patients were separated into two groups. Group A consisted of patients with a diagnosis of Charcot and a hemoglobin A1C 3 6.5%, while group B consisted of patients with a diagnosis of Charcot and hemoglobin A1C < 6.5%. Statistical analysis was then performed to determine the relative risk of a BKA in patients exposed to a hemoglobin A1C 3 6.5%, compared to those with a hemoglobin A1C < 6.5%. Only patients with a documented A1C around the time of diagnosis were included. Results: From 2015 to 2021, 80 patients were diagnosed with Charcot Foot. Of these patients, 59 met our inclusion criteria. Of the 59 patients, 20.3% (12/59) went on to require a BKA and 79.6% (47/59) did not. In our cohort, 54.2% of patients had a hemoglobin A1C 3 6.5% and 45.8% (27/59) had a hemoglobin A1C < 6.5%. The relative risk of BKA in patients with an A1C 3 6.5% was 2.5 (95% CI: 0.76-8.4; p=0.13). Conclusion: Charcot Foot is a debilitating and potentially limb-threatening complication. While our results suggest an associated increased risk of BKA in patients with an A1C 3 6.5%, there was no statistical significance found. As such, further investigation is needed.